Degree of Integration Between Occupational Safety and Health Programs and Wellness Programs: First-year Results From an Insurer-Sponsored Wellness Grant for Smaller Employers. Issue 9 (September 2019) - Meyers, Alysha R.; Al-Tarawneh, Ibraheem S.; Bushnell, P. Timothy; Wurzelbacher, Steven J.; Lampl, Michael P.; Tseng, Chih-Yu; Turner, Dayona M.; Morrison, Carol A.
Abstract : Objective: The aim of this study was to describe levels of integration between occupational safety and health (OSH) and workplace wellness programs/practices/policies ("programs") among participants in an insurer-sponsored wellness grant program. Methods: We analyzed survey responses about year 1 of an insurer-sponsored grant to start a wellness program from 220 small- and medium-sized employers. Responses yielded 25 indicators of OSH-wellness integration, and 10 additional indicators to summarize multiple responses. Results: At least half of the employers ( N  = 220) reported some level of integration within five of seven categories of OSH-wellness integration. Employers sometimes considered ergonomics, safety, or substance exposure hazards while designing their wellness program (15%) or reduced such hazards to support their wellness program (24%). Few meaningful differences were observed by employer size. Conclusions: Although high levels of integration were unusual, some degree of integration was common for most indicator categories.